Utilization of Waste Graphite for the Sustainable Production of Silicon Carbide - Charikleia Vourgidi; Ioanna Giannopoulou; Apostolos Kourtis; Maria Magganiari; Anthimos Xenidis (Materials Proceedings, 2024)
Silicon carbide (SiC) is a great material for high-tech applications due to its unique mechanical, thermal and electrical properties. The Acheson method that is currently used for its production necessitates temperatures between 2000 and 2500 °C, resulting, thus, in a significant environmental footprint. In this work, an innovative approach for the production of SiC at temperatures below 1000 °C is investigated using metallic magnesium to reduce silica and utilizing waste graphite from the industrial production of graphite molds for non-ferrous metallurgy. According to the results, the molar ratios of silica to graphite and magnesium mainly affected the formation of SiC.